Analysis of the Effect of Supply Chain Management on the Competitiveness of Coastal Fisherman Communities in North Minahasa District. (25th February 2021) - Karuntu, Merlyn Mourah; Palandeng, Indrie Debbie; Rogi, Mirah Helen
No abstract available